Potassium channels as promising new targets for pharmacologic treatment of tinnitus: Can Internet-based ‘crowd sensing’ initiated by patients speed up the transition from bench to bedside? - Langguth, Berthold (2016)
Fil: Langguth, Berthold. University of Regensburg; Alemania